Công nghệ số và năng suất lao động của doanh nghiệp Việt Nam: Mô hình đánh giá và kết quả - Đặng Thị Việt, Đức; Đặng Phong, Nguyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The article aims to clarify the impact of digital technology applications on labor productivity using quantitative methods and reliable data from Vietnamese enterprises. Data was collected over two enterprise survey years 2018 and 2020 to capture the change in digital technology adoption and impact over time. The estimated results show that digital technology application, reflected in five groups of software and specialized information systems, organization of digital technology application, digital skills of employees, application advanced digital technology, and digital information security, has a positive impact on the labor productivity of enterprises. The study also shows that the intensity of the impact of digital technology applications on labor productivity of Vietnamese enterprises has increased over the period from 2018 to 2020. This proves that Vietnamese enterprises know how to exploit and make better use of digital technology for business purposes.
Keywords: Digital Economy; Digital Technology; Impact; Productivity; Vietnam